PELAKSANAAN PRINSIP BEBAS AKTIF DI BAWAH KEPEMIMPINAN SUSILO BAMBANG YUDHOYONO (2004-2014) - Widia Wahyuni, - (2018)
This under graduate academic exercise is titled "İmplementation of The Principle İndependent Active Under The Leadership of Susilo Bambang Yudhoyono (2004-2014)". Writing this under graduate academic exercise background by the interest of writers to understand the policies taken by the government of Susilo Bambang Yudhoyono in maintaning the independent active politics. Based on this background, the author makes the following research questions; (1) How internal and external social political conditions at induring the leadership of SBY? (2) How is foreign policy of Indonesia during the leadership of SBY as implemented by the foreign minister Hassan Wirajuda (2004-2009) and the foreign minister Marty Natalegawa (2009-2014)? (3) How the impact of the implementation of independent active principles the leadership in SBY (2004-2014) to image of Indonesia in the international association?. The method used in the study of the historical method. In reviewing the research question, author uses an interdisciplinary approach by using some of the concepts of political science. SBY is the first Indonesian president of popular choice, SBY ruled for two periods 2004-2009 and 2009-2014. During the early period of his reign, President SBY focuses on solving internal problems, especially related to conflicts that distrub security and order. After that then the government SBY must deal with international social and political conditions that undergo major changes, the cause of these changes is the strengthening of globalization. President SBY assisted by Wirajuda and Natalegawa as foreign ministers in carrying out soft power foreign policy with constructive approach. In the second period of his administration SBY introduced Indonesian foreign policy with slogan million friends zero enemy. The government of SBY able to restore the positive image of Indonesia, especially in the association and it contributes to the progress of the Indonesian economy. ---- Skripsi ini berjudul "Pelaksanaan Prinsip Bebas Aktif di Bawah Kepemimpinan Susilo Bambang Yudhoyono (2004-2014)". Penulisan skripsi ini dilatar belakangi oleh ketertarikan penulis untuk memahami kebijakan-kebijakan yang diambil oleh pemerintah SBY dalam mempertahankan politik bebas aktif. Berdasarkan latar belakang tersebut, penulis membuat pertanyaan penelitian sebagai berikut; (1) Bagaimana kondisi sosial politik dalam dan luar negeri pada masa kepemimpinan SBY? (2) Bagaimana kebijakan luar negeri Indonesia pada masa kepemimpinan SBY sebagaimana yang dilaksanakan oleh Menteri Luar Negeri Hassan Wirajuda (2004-2009) dan Menteri Luar Negeri Marty Natalegawa (2009-2014)? (3) Bagaimana dampak pelaksanaan prinsip bebas aktif pada masa kepemimpinan SBY (2004-2014)?. Metode yang digunakan dalam penelitian ini adalah metode historis. Dalam mengkaji pertanyaan penelitian, penulis menggunakan pendekatan interdisipliner dengan beberapa konsep dari ilmu politik. SBY adalah presiden pertama yang dipilih oleh rakyat secara langsung, SBY memerintah selama dua periode 2004-2009 dan 2009-2014. Pada masa periode awal pemerintahannya, Presiden SBY memfokuskan pada penyelesaian permasalahan dalam negeri terutama terkait konflik yang mengganggu keamanan dan ketertiban. Setelah urusan dalam negeri terselesaikan Pemerintah SBY berhadapan dengan kondisi sosial politik internasional yang mengalami perubahan besar, penyebab dari perubahan tersebut adalah menguatnya peranan globalisasi. Presiden SBY dibantu Menlu Wirajuda (2004-2009) dan Menlu Natalegawa (2009-2014) dalam melaksanakan kebijakan luar negeri soft power yang dibarengi dengan pendekatan konstruktif. Pada periode kedua Pemerintahan SBY memperkenalkan kebijakan luar negeri dengan semboyan one million friends zero enemy. Pemerintahan SBY mampu mengembalikan citra positif Indonesia khususnya dalam pergaulan internasional dan hal tersebut memberikan kontribusi bagi kemajuan perekonomian Indonesia.